Exploring bison producers' access to veterinary services in Ontario, Canada - Lambrou, Natassia H.; Winder, Charlotte B.; Spence, Kelsey L. (Frontiers in Veterinary Science, 2024)
IntroductionAccess to veterinary services is integral for animals of all species. These services play a crucial role in maintaining their health and welfare and maintaining a healthy, safe, and sustainable food system. Research has consistently shown that rural communities face challenges accessing veterinary services, with livestock producers outlining several barriers including cost, inadequate infrastructure, and delays in receiving treatments. Research on bison producers' access to veterinary services is limited, prompting our investigation to address this gap in knowledge. This qualitative study aimed to describe Ontario bison producers' current access to veterinary services and identify how any barriers, as perceived by producers, might impact their herd health and management practices.MethodsOntario bison producers were invited to participate in virtual focus groups to share their perspectives on their access to veterinary services. Audio from the focus groups was recorded, transcribed verbatim, and analyzed using reflexive thematic analysis.ResultsDespite all participants indicating they had access to veterinary services, they also encountered obstacles and expressed concerns accessing and utilizing these services. Two overarching themes were identified: producers were concerned about the future stability and costs associated with bison farming, and they had a desire to improve bison-specific knowledge among veterinarians servicing their farms. Producers suggested several strategies to address these concerns, including improving collaborations with veterinary organizations, like the College of Veterinarians of Ontario, to increase veterinarians' exposure to bison, building stronger relationships between producers and their veterinarians, monetary incentives for established food animal veterinarians, and providing financial support to prospective food animal veterinarians.DiscussionThe findings of this study demonstrate that although bison producers in our sample had access to veterinarians, they may not fully utilize the services or find their access entirely beneficial. Future research into the veterinarian perspective would allow for greater insights into these barriers, adding additional value and contributing to a more wholistic understanding of the topic.